2008
DOI: 10.1186/1744-8069-4-42
|View full text |Cite
|
Sign up to set email alerts
|

Direct Activation of Transient Receptor Potential Vanilloid 1(TRPV1) by Diacylglycerol (DAG)

Abstract: The capsaicin receptor, known as transient receptor potential channel vanilloid subtype 1 (TRPV1), is activated by a wide range of noxious stimulants and putative ligands such as capsaicin, heat, pH, anandamide, and phosphorylation by protein kinase C (PKC). However, the identity of endogenous activators for TRPV1 under physiological condition is still debated. Here, we report that diacylglycerol (DAG) directly activates TRPV1 channel in a membrane-delimited manner in rat dorsal root ganglion (DRG) neurons. 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 35 publications
(52 reference statements)
5
71
0
2
Order By: Relevance
“…Although lipid metabolite products such as hydroperoxyeicosatetraenoic acid and anandamide have been suggested as candidate molecules for mediating GPCR activation of TRPV1 (Hwang et al, 2000;van der Stelt et al, 2005), the identities of endogenous ligands for TRPV1 at the pathophysiological conditions, especially in the central neurons, are still debated. We have recently demonstrated that DAG is a novel endogenous ligand of TRPV1 (Woo et al, 2008). In the present study, we provide further strong evidences that group l mGluR5 activates the TRPV1 channel in a membrane-delimited manner and DAG mediates functional coupling of group l mGluR5 and TRPV1 on central presynaptic terminals of sensory neurons.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Although lipid metabolite products such as hydroperoxyeicosatetraenoic acid and anandamide have been suggested as candidate molecules for mediating GPCR activation of TRPV1 (Hwang et al, 2000;van der Stelt et al, 2005), the identities of endogenous ligands for TRPV1 at the pathophysiological conditions, especially in the central neurons, are still debated. We have recently demonstrated that DAG is a novel endogenous ligand of TRPV1 (Woo et al, 2008). In the present study, we provide further strong evidences that group l mGluR5 activates the TRPV1 channel in a membrane-delimited manner and DAG mediates functional coupling of group l mGluR5 and TRPV1 on central presynaptic terminals of sensory neurons.…”
Section: Discussionsupporting
confidence: 55%
“…To provide further evidences on the membrane-delimited activation of TRPV1, we used Ca 2ϩ imaging in the present study. As indicated in our previous study (Woo et al, 2008), one possible mechanism of this pathway would be direct interaction between DAG and TRPV1. To investigate this possibility, we used Y511A mutants of TRPV1 (Jordt and Julius, 2002) transiently expressed in HEK293 cells.…”
Section: Dag Directly Activates the Trpv1 Channel In A Membrane-delimmentioning
confidence: 99%
See 2 more Smart Citations
“…However, histamine-induced itch appears to require both PLC␤3 and TRPV1, which suggests that TRPV1 can function as an effector molecule downstream of PLC␤3. In support of this proposal, a recent electrophysiological study (25) demonstrated that TRPV1 is directly activated by diacylglycerol (DAG), which is produced by hydrolysis of PIP 2 , a substrate of PLC␤3. There may be other mechanisms as well for TRPV1 activation in histamine-mediated signaling (10).…”
Section: The Molecular Specificity Of G␣q-plc␤ Intracellular Signalinmentioning
confidence: 79%